Determining the Adsorption Free Energies of Small Organic Molecules and Intrinsic Ions at the Terrace and Steps of Calcite - Aufort, Julie; Schuitemaker, Alicia; Green, R.; Demichelis, Raffaella; Raiteri, Paolo; Gale, Julian (AMER CHEMICAL SOC, 2022)
The adsorption of small molecules containing two different organic functional groups at terrace and step sites on the {101¯ 4} surface of calcite at the interface with aqueous solution was studied using free energy methods. For comparison, the adsorption free energies of the component ions of calcium carbonate were also determined at the same sites. Polarizability was taken into account through using a force field developed for calcium carbonate based on the AMOEBA model that contains static multipoles and self-consistent induced dipoles. The influence of including polarization was examined by comparing to data obtained with a fixed charge rigid-ion model. The strong hydration layers above the basal plane of calcite were shown to hinder the direct attachment of the small species studied, including the constituent ions of the mineral. Only the species bearing an amino group, namely, methylammonium and glycine, demonstrated favorable adsorption free energies. The ability of amino groups to more readily pass through the hydration layers than carboxylate and carbonate groups can be explained by their weaker solvation free energies, while the carbonate ions within the calcite surface with which they bind are also less strongly hydrated than calcium ions. Acetate, glycine, and methylammonium were all found to be able to directly bind to one growth site at the acute step of calcite. This is at variance with results obtained with a rigid-ion model in which all binding free energies are endergonic. Thus, including polarization allows for a description of the adsorption process that is more consistent with experimental observations, particularly at calcite steps, and for determination of more reliable atomic-scale mechanisms for calcite growth and its modification by organic additives. Even with polarization, the organic functional groups considered only exhibit moderate binding to calcite steps with adsorption free energies not exceeding -13 kJ/mol.